2019
DOI: 10.1111/hepr.13446
|View full text |Cite
|
Sign up to set email alerts
|

Hypovascular hepatic nodules as a predictive factor for transcatheter arterial chemoembolization refractoriness in hepatocellular carcinoma

Abstract: Aim Intermediate‐stage hepatocellular carcinoma (HCC) targeted for transcatheter arterial chemoembolization (TACE) corresponds to a highly heterogeneous population for whom the factors predicting TACE efficacy have not been established. This study aimed to evaluate the impact of hypovascular hepatic nodules coexisting with intermediate‐stage HCC as a significant predictive factor for TACE refractoriness. Methods A total of 66 patients with intermediate‐stage HCC who received initial TACE were retrospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In view of an optimal treatment allocation, several studies tried to identify preoperative imaging-based predictive factors for good response to chemoembolization, mainly based on tumor size, growth rate, margins, location, and, especially, grade of hypervascularization in the arterial phase [10][11][12][13][14]. Up to approximately 30% of HCCs, however, lack a clear arterial phase hyper-enhancement [15,16], including very early HCCs, poorly differentiated HCCs, and HCC nodules with small hypervascular foci [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In view of an optimal treatment allocation, several studies tried to identify preoperative imaging-based predictive factors for good response to chemoembolization, mainly based on tumor size, growth rate, margins, location, and, especially, grade of hypervascularization in the arterial phase [10][11][12][13][14]. Up to approximately 30% of HCCs, however, lack a clear arterial phase hyper-enhancement [15,16], including very early HCCs, poorly differentiated HCCs, and HCC nodules with small hypervascular foci [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…TACE is the standard and effective therapy for intermediate-stage HCC. However, this course of treatment can be limited in terms of effectiveness as patients present TACE refractoriness (Arizumi et al, 2017;Maesaka et al, 2020). For patients with TACE FIGURE 3 | Nomogram to predict early TACE refractoriness, each predictor corresponds to a specific point by drawing a line straight upward to the points axis.…”
Section: Discussionmentioning
confidence: 99%
“…Transarterial chemoembolization (TACE) is the standard therapy for intermediate-stage HCC, which is accepted by several guidelines (Piscaglia and Ogasawara, 2018;Lee et al, 2019). However, it has been reported that not all HCC patients respond to TACE because the patients selected for TACE correspond to a highly heterogeneous population, covering a wide range of tumor burdens, liver function and treatment histories (Maesaka et al, 2020;Xue et al, 2020). Furthermore, repeated TACE procedures could gradually lead to TACE refractoriness, and some patients even show TACE failure at the very beginning of their treatment (Maesaka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in patients with very early and early HCC, the presence of hypovascular hepatic nodules represents a significant risk factor for recurrence and a bad prognosis after treatment; this is a contraindication to the procedure in these patients [159] . Moreover, a CT image analysis method known as the parametric response map approach is more sensitive for finding changes in the response to treatment than the conventional approach based on the recap of statistics assessed on a region of interest.…”
Section: Imaging Predictive Factorsmentioning
confidence: 99%